Modeling of spectrum demands through hybrids of analytic hierarchy process and integer programming - Ramli, Razamin; Jamaluddin, Faathirah; Engku Abu Bakar, Engku Muhammad Nazri; Alias, Mohamad Yusoff; Mahat, Nor Idayu; Abd Karim, Mohd Zaini; Ang, Chooi Leng (IACSIT Press, 2011)
As wireless technology advances, demand for spectrum bandwidth increases and thus, spectrum has become scarce. As a scarce resource, spectrum bandwidths need to be efficiently allocated to potential service providers. Hence, this paper first reviews current approaches on how spectrum bandwidths are being allocated to the service providers. Then we present an efficient integrated approach in allocating spectrum volumes, whereby the approaches of Analytic Hierarchy Process and Integer Programming are integrated and applied to produce systematic and consistent allocation results. The integrated approach is able to cater multi-criteria problems through determination of suitable weights and computations, which exhibits a more efficient alternative as compared to the existing approaches.The illustrations revealed that the integrated approach indeed has the potential to be implemented and gives an alternative to the current existing approaches.